Georgy girl - Narizzano, Silvo 1927-2011; Goldston, Robert 1927-; Mason, James cast; Bates, Alan 1937-2003; Redgrave, Lynn 1943-2010 (Columbia Pictures, 1966)
Warm, winning and fun-loving Georgy doesn't fit into the swinging London social scene, but yearns for a traditional life and traditional romance. She rooms with the sultry, moody Meredith, who lives for the moment and the next available man, Currently, that man is Joe. When Meredith and Joe have a baby, Meredith is indifferent, but Georgy id thrilled and winds up taking care of the baby. Now radiant with motherly feeling, Georgy suddenly becomes the object of desire of a wealthy widower and Joe!.